2004
DOI: 10.1002/uog.992
|View full text |Cite
|
Sign up to set email alerts
|

Likelihood ratio for trisomy 21 in fetuses with absent nasal bone at the 11–14‐week scan

Abstract: Objective To update the likelihood ratio for trisomy 21 in fetuses with absent nasal bone at the 11-14-week scan. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
107
1
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(122 citation statements)
references
References 22 publications
5
107
1
9
Order By: Relevance
“…Several studies have demonstrated a strong between an absent nasal bone at 11-14 weeks of gestation and trisomy 21 [32][33][34]. And in the combined data from these studies, the fetal nasal bone was absence in 69% of fetus with trisomy 21 [26].…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have demonstrated a strong between an absent nasal bone at 11-14 weeks of gestation and trisomy 21 [32][33][34]. And in the combined data from these studies, the fetal nasal bone was absence in 69% of fetus with trisomy 21 [26].…”
Section: Discussionmentioning
confidence: 91%
“…The midfacial hypoplasia in Down syndrome can be shown by the shorter maxillary length, absent nasal bone, and frontomaxillary facial angle, which was significantly greater in fetuses with trisomy 21 than in euploid fetuses. [18][19][20][36][37][38][39] In fetuses with trisomy 18, it was reported that the frontomaxillary facial angle was greater and the mandibulomaxillary facial angle was smaller than those in normal fetuses because of midfacial hypoplasia and micrognathia or retrognathia. Fetal alcohol syndrome is characterized by evidence of growth restriction, neurodevelopmental abnormalities, and a characteristic pattern of facial anomalies, such as short palpebral fissures, midfacial hypoplasia, a smooth philtrum, minor ear anomalies, and micrognathia.…”
Section: A B Cmentioning
confidence: 99%
“…Detection of the presence or absence of a nasal bone has been found to be of value in the assessment of aneuploidy in the first trimester of pregnancy (risk assessment for trisomy 21). [16][17][18][19][20] Cicero et al 20 reported that the nasal bone was absent in 113 (0.6%) of the 20,165 chromosomally or phenotypically normal fetuses and in 87 (62.1%) of the 140 fetuses with trisomy 21. 3D sonography allows a midsagittal section of the fetal face to be obtained by utilizing the three orthogonal planes, and avoids the pitfall of obtaining a parasagittal view, which could lead to false-negative results.…”
Section: Facial Abnormalitiesmentioning
confidence: 99%